The Role p-53 Protein in Oncogenesis of Non-hodgkin Malignant Lymphomas - Aurelian Udristioiu; Adina Martin; Alexandru Giubelan; Liviu Martin; Buciu Gabriel; Papurica Maria Daniela; Manole Cojocaru; Delia Nica-Badea (Current Innovations in Medicine and Medical Science Vol. 6, 2022)
Scope: The aim of this paper was to highlight the stages of Chronic Lymphocytic Leukemia type B (CLL-B), which did not meet the standard treatment criteria for malignant hematological diseases due to mutations in the P-53 gene, with progression to Richter Syndrome. Method: The frequency of p-53 protein expression in 85 patients diagnosed with CLL was analyzed by the Enzyme Linked Immune-Absorbent Assay (ELISA) technique to investigate the relationship of this protein to the stage of the disease, as well as the impact on response to treatment and survival. Results: The frequency of increased positivity of the protein with the modified structure, the isoform, p-53 in type B CLL, was 17% in the 85 cases initially included in the study. The percentage of p-53 protein isoforms, positive above normal value, with very high values, 50, 60, respectively 140 \(μ\)g / dl was found in the percentage of 3.5% with the transformation of CLL into non-Hodgkin’s malignant lymphomas, (NHL) type Diffuse Large Lymphoma, (DLL) or in Mantle Lymphoma, from Richter syndrome. Conclusions: In the context of a heterogeneous condition such as LL-B, this cheap and safe method, ELISA seems to provide a useful prognostic tool capable of identifying patients who can be considered candidates for therapeutic, targeted, personalized strategies.